Crossing Professional Thresholds with Networked Learning? An Analysis of Student E-Portfolios Using the Threshold Concept Perspective - Arnold, Patricia; Kumar, Swapna (Proceedings of the International Conference on Networked Learning, 2014)
Investigations in networked learning often focus on specific educational designs, questions of appropriate supporting technologies, community building issues or social network analysis. In this paper we look at networked learning from a different angle: Students who are working professionals in the social field and who study for a BA degree in social work via networked learning enter the program with a professional background in social work. Faculty in these programs often estimate that these students benefit a lot in their professional development during the course of their studies but so far there is little evidence for this assessment. Also, there is a lot of skepticism as to whether it is possible to integrate scientific knowledge and interweave it with professional experience via networked learning. In our study we use the threshold concept perspective to develop a methodology to analyze whether students do "cross professional thresholds" in the study program. The purpose of this pilot study, therefore, is twofold: Firstly, we want to gain evidence whether or not students are crossing thresholds in the course of the program via networked learning. Such evidence could in the long-term provide important arguments for setting up similar study programs via networked learning for non-traditional student groups. Secondly, we want to describe a methodology that can be used for regular impact studies. We use the case of a distance education BA-program in social work in Germany, delivered via networked learning. We look at students’ e-portfolios created to document and reflect on their learning journeys in an online module that comprises the second half of the study program. In addition, we report on our approach to find indicators for "crossing thresholds" in this rich empirical data. Results of the analysis show some relevant examples of students’ threshold crossings in the field of social work. Finally, we reflect critically upon the methodology used in order to refine and further develop it. The results of this study will be relevant for higher education stakeholders such as university management, faculty, and students themselves as well as for researchers involved with impact studies of networked learning.